Laparoscopic management of post coital vaginal cuff dehiscence after total laparoscopic hysterectomy - Mahendran, Shanmugapriya; Ghorpade, Niteen; Pal, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Vaginal cuff dehiscence is a rare postoperative complication following total laparoscopic hysterectomy. Timely recognition and surgical repair is essential for successful management. A 39 year old female, para2 live2, presented with symptoms of watery vaginal discharge and vague pelvic pain associated with sexual activity, three months after total laparoscopic hysterectomy. Per speculum examination revealed a 3 cm rent in vaginal cuff without any evidence of bowel evisceration. Diagnostic laparoscopic assessment along with vaginal cuff repair done. The incidence of vaginal cuff dehiscence after total laparoscopic hysterectomy may be attributed to over use of electrocautery, prolonged inflammatory response, and suturing techniques. Abdominal, vaginal and laparoscopic approaches are the routes for repairing vaginal cuff dehiscence. However, it depends on clinical presentation and surgeon’s expertise. Careful history and examination guides the clinician to arrive at correct diagnosis and knowledge of appropriate medical and surgical interventions are of paramount importance for treatment of vaginal cuff dehiscence.